Скказки о животных для малышей - Сальникова Людмила (Серия "Любимые сказки малышам", 2013)
Экземпляры: ф. 2 (20160226) / Инвентарный номер: 103661 / Цена: 180.00 / Авт.знак: С 42 / ГРНТИ: 17.82 / ББК: 84(2=411.2)